Teach Aquaculture Curriculum: How Big Is That Pond? - Cortney L. Ohs; Amber L. Garr; R. Leroy Creswell; Elisa J. Livengood; Brian E. Myers; Carlos V. Martinez; Frank A. Chapman; Craig S. Kasper (EDIS, 2010)
FA170, a 5-page activity by Cortney L. Ohs, Amber L. Garr, R. Leroy Creswell, Elisa J. Livengood, Brian E. Myers, Carlos V. Martinez, Frank A. Chapman, and Craig S. Kasper, is activity 5 of the Teach Aquaculture Curriculum. In this activity for grades 5-12, students will learn to calculate the volume, surface area, stocking densities of fish, and chemical application amounts for various sizes of ponds. Includes student performance standards. Published by the UF School of Forest Resources and Conservation, Program in Fisheries and Aquatic Sciences, May 2010.